The Plasma Electrolysis Phenomenon in a Two-Compartment Reactor for Chlor-Alkali Production - Saksono, Nelson; Abqari, Fakhrian; Bismo, Setijo (UI Scholars Hub, 2013)
Chlor-alkali is one of the most important processes in the chemical industry. It produces chlorine and caustic soda, which become the main feedstock of daily products. The aim of this study is to report the phenomenon of plasma electrolysis and how it can be used in chlor-alkali production for more efficient energy consumption. When the plasma is formed, the current fluctuates and gradually declines. Plasma electrolysis begins with the process of electrolysis itself. Due to Joule heating, gas bubbles are formed and a sheath is made on both electrodes, resulting in the plasma field. Plasma electrolysis can be identified by its radical production. The higher the voltage and concentration, the greater the production of radicals. In 10 minutes or less, the number of OH radicals produced can reach 4 ppm at 400 V and 0.1 M. This amount is relatively small and is caused by other reactions consuming OH radicals to form other radicals such as chlorine. The energy consumption of plasma electrolysis in this study can reach 16 kJ/mmol Cl2 at 0.5 M NaCl solution.